Booms, bubbles, and busts in US stock markets - Western, David L. (London ; New York : Routledge, 2004)
This book provides an overview of the inner workings of the US stock market. It also examines the current conditions before looking back to the events of the past century - The Great Depression, the 1970s oil crisis, the party-for-the-rich atmosphere of the 1980s and the emergence of the new economy.
Includes bibliographical references (p. [226]-231) and index.
lje 12/07/16
Loans
Keywords: Stocks; Investments